An Essay Concerning Human Understanding. Volume One - Locke, John (Saga Egmont, 2022)
‘An Essay Concerning Human Understanding’ is philosopher John Locke\'s pioneering examination of the origins of human knowledge and understanding. First published in 1690, it set the agenda for modern philosophy and influenced psychology and political theory. ‘An Essay Concerning Human Understanding. Volume One,’ covers Locke’s attempts to discover where our ideas come from, what it means to have an idea and what an idea actually is. He also discusses theories on free will and personal identity, outlining the notion of the blank slate at birth or tabula rasa, which is then filled in by experience of the world. Regarded as Locke’s most powerful and important philosophical work, ‘An Essay on Human Understanding’ still resonates today. John Locke (1632-1704) was an English philosopher and political theorist, whose work built the foundations of modern liberalism, political theory and economics. Commonly known as the \"Father of Liberalism\" he is widely regarded as one of the most influential Enlightenment thinkers. Locke’s ideas on ‘identity’ and ‘self’ and the notion we are born with a ‘blank slate’, helped shape the work of philosophers such as Kant, Rousseau and Voltaire, while his essays on religious tolerance were an early model for the separation of church and state. The American Declaration of Independence was influenced by Locke’s political ideas on government, creating the foundation for the freedoms enjoyed by Americans today.